1989
DOI: 10.1159/000110177
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Motor Neuron Disease in Two Danish Counties

Abstract: A total of 186 cases of motor neuron disease (MND) was identified in two Danish counties during the period 1974–1986. The average annual incidence rate was 1.4/100,000 population, and the male:female ratio of incidence rates was 1.5. Mean age at diagnosis was 64.3 ± 10.0 years. The incidence rates increased significantly with advancing age and reached a maximum at age 60–79 years, followed by a nonsignificant decrease. The average point prevalence was 3.1/100,000 population. Bulbar symptoms were part of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 17 publications
(37 reference statements)
2
11
0
Order By: Relevance
“…This is comparable with the rates reported for Eu rope and with the findings in Switzerland and in Denmark [30,10], Recently, the inci dence we found was 2.0 and compared to the European rates is by far the highest [31,32], The previous Italian surveys gave an inci dence estimate ranging from 0.5 to 1.2 per 100,000 [33][34][35][36][37][38][39]. The higher rate found in Reggio Emilia probably reflects the particu lar attention paid to this disease by the only neurology department existing in the area.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is comparable with the rates reported for Eu rope and with the findings in Switzerland and in Denmark [30,10], Recently, the inci dence we found was 2.0 and compared to the European rates is by far the highest [31,32], The previous Italian surveys gave an inci dence estimate ranging from 0.5 to 1.2 per 100,000 [33][34][35][36][37][38][39]. The higher rate found in Reggio Emilia probably reflects the particu lar attention paid to this disease by the only neurology department existing in the area.…”
Section: Discussionsupporting
confidence: 92%
“…More recent mortality and incidence stud ies have suggested greater population varia tions and a possible increase in ALS occur rence [9]. They also suggested an increase in the mean age of onset in the last few years, with a peak in the 7th decade and a rapid fall in older age [10]. In Rochester, Minn., motor neuron rates increased progressively with age [ 11].…”
Section: Introductionmentioning
confidence: 98%
“…Many authors also reported a significant difference between the survival of patients with spinal and those with bulbar onsets; the serious na ture of the bulbar forms has been pointed out [17][18][19][20]22], The mean age at onset was significantly higher in the bulbar forms than in the com mon forms of the disease. In our series, onset of the bulbar form occurred 6 years later than that of the common forms, which was compa rable to the 4-year difference reported by Christensen et al [ 15], Murros and Fogelholm [22] noted that the older patients had a higher incidence of bulbar than peripheral onset forms, as did Hojer-Pedersen et al [23], Nor ris et al [19] and Eisen et al [17], while Prout et al [24] observed that the onset of the bulbar forms occurred around 10 years later than that of the peripheral forms.…”
Section: Discussionsupporting
confidence: 87%
“…[7][8][9][10][11][12] As biologically-active CAM, such as herbal products, are being sought by cancer patients with increasing frequency, 18 conventional providers require an understanding of the CAM selection process to promote open disclosure and provide appropriate guidance and professional support, 19,20 particularly at the time of the patient receiving chemotherapy. This review aims to describe existing literature on the use of CAM by cancer patients receiving chemotherapy, and to identify gaps and issues that need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] The potential for adverse outcomes associated with taking biologically-active CAM concurrently with chemotherapy is through interactions that may change the efficacy of chemotherapy. 13 By contrast, natural product-derived CAM that has no evidence for biological activity by virtue of their extreme levels of dilution, e.g.…”
mentioning
confidence: 99%